Amphetamine improves mouse and human attention in the 5-choice continuous performance test. (August 2018) - MacQueen, David A.; Minassian, Arpi; Kenton, Johnny A.; Geyer, Mark A.; Perry, William; Brigman, Jonathan L.; Young, Jared W.
Abstract: Non-medical use of prescription stimulants amongst college students is common, with claims of cognitive and academic benefits. The mechanism, magnitude, and pervasiveness of the cognitive enhancing effects of stimulants in healthy adults remain poorly understood however. The present study determined the effects of dextroamphetamine (D-amp) on the 5-choice continuous performance test (5C-CPT) of attention in healthy young adult humans and mice. A mixed gender sample received placebo (n = 29), 10 (n = 17) or 20 mg D-amp (n = 25) in a double-blind fashion before 5C-CPT testing. In addition, male C57BL/6J mice were trained on a touchscreen adaptation of the 5C-CPT and tested after receiving saline or D-amp (0.1, 0.3, 1.0 mg/kg; n = 8/dose). In humans, D-amp significantly improved 5C-CPT performance. Both doses improved signal detection driven by increased hit rate (reduced omissions). Both doses also improved response accuracy and reduced hit reaction time (HRT) variability. In mice, similar effects (improved signal detection, hit rate, and response accuracy) were observed at the moderate dose (0.3 mg/kg). In contrast to human participants however, no effect on HRT variability was detected in mice, with no effect on HRT in either species. Human 5C-CPT performance was consistent with prior studies and consistent with alternative CPT paradigms. The performance of C57BL/6J mice on the touchscreen 5C-CPT mirrored performance of this strain on 5-hole operant chambers. Importantly, comparable facilitation of attention with D-amp was observed in both species. The 5C-CPT provides a cross-species paradigm by which the cognitive enhancing properties of stimulants and the neural underpinnings of attention can be assessed. Graphical abstract: Image 1 Highlights: The 5C-CPT can be conducted in humans and mice. Mouse touchscreen performance is consistent with 5-hole operant chambers. D-amphetamine (D-amp) treatment improved 5C-CPT performance across species. D-amp similarly affected hit rate and d prime without increasing false alarms.